High-groove music boosts self-selected running speed and positive mood in female university students - Kazuya Suwabe; Satoshi Kawase (Frontiers in Sports and Active Living)
IntroductionApproximately 27.5% of adults worldwide fail to meet the recommended 150 min per week of moderate-to-vigorous physical activity. Music is a powerful tool that enhances positive affective responses and exercise adherence. However, little is known regarding which types of music are most effective in enhancing these benefits. Groove, which induces a sensation of “wanting to move to the music” and is associated with positive affective responses, may help make self-paced exercise more active and pleasant. Therefore, in this study, we examined the effects of high-groove (HG) music on self-paced exercise and mood responses.MethodsThirty-eight university students (18 males) participated in this randomized crossover study under two experimental conditions. The participants ran on a treadmill for 10 min at a self-selected comfortable speed while listening to HG and low-groove (LG) music playlists.ResultsThe HG playlist received higher groove ratings than the LG playlist. Self-selected running speed and positive mood responses (vitality and arousal) were greater under the HG condition only in women. Exercise intensity measured using heart rate and the rate of perceived exertion was comparable between the conditions. The groove ratings for the HG playlist positively correlated with speed (HG-LG) and vitality changes under the HG condition (post-pre).ConclusionThese results suggest that HG music promotes a positive mood response and exercise adherence, particularly in female students. Moreover, the observed sex difference suggests that individual differences in music perception may also influence exercise behavior. Focusing on groove, a musical characteristic distinct from tempo and volume, our study provides a more comprehensive understanding of music that is compatible with exercise, while also examining potential sex differences in its effects on self-paced exercise and mood responses. These findings contribute to health promotion by encouraging active living via physical exercise.